OFR-44-79 Monitoring Of Mine Air Blast Pollutants From Six Explosives Tested In An Underground Mine - Duane L. Abata (The National Institute for Occupational Safety and Health (NIOSH), 1978)
Toxic gases produced by the detonation of six explosives were measured in an underground hardrock metal mine during actual mining operations. The six explosives included two semi-gelatin dynamites, three slurry explosives and an ammonium-nitrate, fuel-oil/ammonia dynamite combination. Explosives were detonated at the face of a drift and the toxic gases produced by the detonation were trapped to the end of the drift by a bulkhead located a short distance away from the face. Toxic gas concentrations were then measured with direct readout instruments and together with the containment volume, the toxic gas volumes per mass of explosive were calculated. Toxic gas measurements were found in the following ranges (ft3/lbm): N02 0.010-0.035; N02, 0.003-0.019; CO, 0.08-0.30; S02, 0.00-0.05; and C02, 0.7-1.8. Results showed that toxic gas production (ft3/lbm) correlated with the densities (kg/m3) and energy densities (kJ/kg) of the explosives tested.